PENGARUH RENCANA INDUK BANDAR UDARA DI PROVINSI KALIMANTAN SELATAN TERHADAP JUMLAH PENUMPANG ANGKUTAN UDARA PADA TAHUN 2020 DAN 2030 - Eriza Islakul Ulmi; Ervina Ahyudanari (Journal of Civil Engineering, 2019)
The Minister of Transportation Regulation No.69 of 2013 set the national master plan of the airport in 2020 and 2030 including the airports in the Province of South Kalimantan. This causes a change in the role of the airport in South Kalimantan so effected on travel pattern change and affect on passengers trip distribution. Therefore, an analysis is needed to predict passenger travel patterns in the future. Data of passenger movement from Syamsudin Noor Airport, Gusti Syamsir Alam Airport, and Bersujud Airport analyzed by Exponential Smoothing Forecasting Method. While Tanjung Warukin airport is analyzed by multiple regression analysis method. The result of this study is in 2020 there is a new route that is Tanjung-Kotabaru predicted as many as 1.773 passengers using the route, it gives influence on demand of airport in Kotabaru that is from 299.203 people will be 300,976 people. The newly operated Tanjung-Banjarmasin route has the potential to survive as indicated by the number of passengers in 2020 of 5942 people.